Il microclima di musei e archivi Nuove tecnologie per il monitoraggio - Redazione Archeomatica (Archeomatica, 2016)
Preserving cultural heritage means today to ensure appropriate environmental conditions to be monitored trough state of- the-art technologies. Testo Saveris technology ensures continuous control, even at a distance, of the main environmental parameters, relativity humidity and temperature, in museums and archives.